REGULATION OF BROADCASTING PROGRAMS IN MACEDONIAN LEGISLATION AND PROTECTION OF DEMOCRATIC VALUES AND PRINCIPLES (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
One of the main goals of regulating broadcasting programs is protectingthe audience from content that can cause harm or damage the consumer.When it comes to advertising consumers should be protected from fake ormisleading advertising messages. Moreover, another goal of regulatingbroadcasting is the protection of the freedom of expression and thedemocratic values of the society, fostering and developing culturalidentity, promoting tolerance and cultural dialogue.In the paper we will address the regulatory measures for the protection ofdemocratic principles and values and individual rights such as: the rightto privacy, protection of dignity, protection against harm, the right to replyand correction. We will also look at the regulatory aspects of theprotection of minors from content that may adversely affect thedevelopment of children, recognition and protection from hate speech,content that incites crime, disorder or racial, religious or ethnic hatred andintolerance.